Effects of Vitamin D on adropine and apoptosis in kidney tissue - Önalan, Erhan; Demircan, Selçuk; Aydin, Suleyman; Kuloğlu, Tuncay; Yalçın, Mehmet Hanifi; Gozel, Nevzat; Dönder, Emir (My University, 2019)
Aim: This study aims to investigate the effects of vitamin D on adropin and apoptosis in rat kidney tissue in the context of theexperimental diabetes model created using streptozotocin (STZ).Material and Methods: 41 male Wistar-albino breed rats of 8-10 weeks were distributed into 5 groups, which consisted of 3 groupswith 7 animals each and 2 groups with 10 animals each. No treatments were applied to the control group. The Buffer group wasadministered with single-dose 0.1 M sodium buffer intraperitoneally (ip). The Vitamin D group was orally administered 200 IU/dayvitamin D. The Diabetes group was injected ip with single-dose 50 mg/kg STZ by dissolving the material in 0.1 M sodium buffer.Results: The biochemical and histological investigations revealed similar serum TOS and TAS levels, and TUNEL positivity andAdropin immunoreactivity for the Control, Buffer, and Vitamin D groups. While TOS levels and TUNEL positivity were significantlyhigher in the Diabetes group compared to the Control group, TAS levels and Adropin immunoreactivity were significantly lower. TheTOS levels and TUNEL positivity were significantly reduced in the Diabetes+Vitamin D group compared to the diabetic group, and TASlevels, adropin immunoreactivity were significantly higher.Conclusion: In conclusion; it was determined that experimental diabetes increased TOS and apoptotic cells and decreased TASand adropin levels in the kidney tissue in experimental diabetes, and that Vitamin D administered as treatment decreased TOSand apoptotic cells and increased TAS and Adropin levels. It was concluded that in order to uncover the role of diabetes in thepathophysiology of its effect on kidney tissue, future studies that consider various experimental diabetes times were necessary
Keywords: Tıbbi Araştırmalar Deneysel; Endokrinoloji ve Metabolizma; Genel ve Dahili Tıp; Patoloji